2012
DOI: 10.4081/or.2012.e14
|View full text |Cite
|
Sign up to set email alerts
|

Regenerate augmentation with bone marrow concentrate after traumatic bone loss

Abstract: Distraction osteogenesis after post-traumatic segmental bone loss of the tibia is a complex and time-consuming procedure that is often complicated due to prolonged consolidation or complete insufficiency of the regenerate. The aim of this feasibility study was to investigate the potential of bone marrow aspiration concentrate (BMAC) for percutaneous regenerate augmentation to accelerate bony consolidation of the regenerate. Eight patients (age 22–64) with an average posttraumatic bone defect of 82.4 mm and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 37 publications
0
23
1
1
Order By: Relevance
“…In any case, the exponential rate of progress in biotechnology has allowed for the immediate application of myriad novel therapies before clear evidence of benefit from randomized clinical trials. In addition to its fundamental science, the ease of on-site preparation of bone marrow-derived cells within the operating theater in the routine clinical setting, minimizing the specific risk of contamination and cell changes during ex vivo cell manipulation, suggests the great therapeutic potential of BMC for autologous cell-based therapy for bone or other tissue repair and regeneration [555,559,567]. …”
Section: Preparations Containing Non-expanded Autologous Stromal Cmentioning
confidence: 99%
“…In any case, the exponential rate of progress in biotechnology has allowed for the immediate application of myriad novel therapies before clear evidence of benefit from randomized clinical trials. In addition to its fundamental science, the ease of on-site preparation of bone marrow-derived cells within the operating theater in the routine clinical setting, minimizing the specific risk of contamination and cell changes during ex vivo cell manipulation, suggests the great therapeutic potential of BMC for autologous cell-based therapy for bone or other tissue repair and regeneration [555,559,567]. …”
Section: Preparations Containing Non-expanded Autologous Stromal Cmentioning
confidence: 99%
“…Bone marrow aspirate and bone marrow concentrate have been proven to be beneficial in tissue regeneration and rejuvenation in both experimental and clinical studies. [34][35][36] Results of histologic evaluations, living tissue imaging, and immunohistological staining showed that bone marrow aspirate and bone marrow concentrate were beneficial in fat survival quality, adipocyte viability, and angiogenesis of fat grafts. These results confirmed our hypothesis, and are in accordance with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…These results confirmed our hypothesis, and are in accordance with previous studies. [34][35][36] Observations of cells expressing both PKH26 and BODIPY and the PKH26/lectin-positive bone marrow concentrate cells demonstrated that bone marrow concentrate cells could improve fat graft survival by multilineage differentiation and participate in adipogenesis and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Both BMAC groups revealed better results than patients treated with bone marrow aspirates without concentration. Gessmann et al [16] investigated the effect of percutaneous application of BMAC into the regenerated bone section in eight patients with tibial bone defects who underwent segmental transport with a modified Ilizarov external fixation device. They found sufficient bone healing and no adverse events in all patients at a mean follow-up of ten months [16].…”
Section: Discussionmentioning
confidence: 99%